2013
DOI: 10.1073/pnas.1312701111
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson-related LRRK2 mutation R1441C/G/H impairs PKA phosphorylation of LRRK2 and disrupts its interaction with 14-3-3

Abstract: Leucine-rich repeat kinase 2 (LRRK2) is a multidomain protein implicated in Parkinson disease (PD); however, the molecular mechanism and mode of action of this protein remain elusive. cAMP-dependent protein kinase (PKA), along with other kinases, has been suggested to be an upstream kinase regulating LRRK2 function. Using MS, we detected several sites phosphorylated by PKA, including phosphorylation sites within the Ras of complex proteins (ROC) GTPase domain as well as some previously described sites (S910 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
140
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(150 citation statements)
references
References 52 publications
7
140
0
Order By: Relevance
“…and threonines interact with 14-3-3, for example LRRK2, p53, and BAD (30,(33)(34)(35)(36). However, the CFTR R-domain interaction with 14-3-3 is exceptional for the large number of interaction sites (nine).…”
Section: Discussionmentioning
confidence: 99%
“…and threonines interact with 14-3-3, for example LRRK2, p53, and BAD (30,(33)(34)(35)(36). However, the CFTR R-domain interaction with 14-3-3 is exceptional for the large number of interaction sites (nine).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies confirmed that PKA is capable of phosphorylating LRRK2 in vitro and in cells, providing indications on the specific phosphorylation sites [43,44]. Li et al [43] showed that phosphorylation of S910 and S935 at the N-terminus of LRRK2 is increased upon forskolin (an adenylyl cyclase activator) treatment and is reduced upon PKA pharmacological inhibition.…”
Section: Molecular Evidence Of Lrrk2-pka Cross-talkmentioning
confidence: 95%
“…Li et al [43] showed that phosphorylation of S910 and S935 at the N-terminus of LRRK2 is increased upon forskolin (an adenylyl cyclase activator) treatment and is reduced upon PKA pharmacological inhibition. A different study reported that PKA directly phosphorylates LRRK2 S1444 in the ROC domain [44]. It is interesting to note that phosphorylation of both S910/ S935 and S1444 promotes LRRK2 binding to 14-3-3 proteins [43][44][45], chaperones that are crucial to control the activity of different signaling molecules [46].…”
Section: Molecular Evidence Of Lrrk2-pka Cross-talkmentioning
confidence: 99%
See 2 more Smart Citations